Rancang Bangun Mesin Penyerut Bahan Baku Anyaman Rotan Dengan Mekanisme Double Roll - Edilla, Edilla; Farhan, Muhammad; Rahmawaty, Made; Jaenudin, Jajang; Ma'a, Mustaza (JURNAL INTEGRASI, 2024)
Rattan Is one of the plants that grow in Indonesia, One of the areas that includes many rattan producers is Riau. Rattan is a plant that is one of the raw materials in the handicraft and furniture industry, therefore, to take advantage of the many rattan plants can be used as a furniture product such as tables, chairs and other handicrafts. The machine is designed using a driving force using a 1 phase electric motor using a double roll pulling system made of rubber and using a blade with a diameter of 5 mm, and this machine also has a safety on the control system so that the AC motor is not easily burned when the current is excessive. This machine can produce 76 rattan sticks per hour with a size 5 mm diameter and 300 cm lenght so that it can increase rattan production more effectively and efficiently. This rattan shaving machine is capable of shaving 300 cm of raw rattan with a diameter of 10-13 mm and the consistency of the thickness produced is 5 mm in diameter with an error rate of 0.22%.